Nucleosome assembly during DNA replication - Verreault, Alain (Henry Stewart Talks, 2009)
Introduction to chromatin structure, Primary function of chromatin: DNA compaction, The nucleosome core particle, De novo nucleosome assembly during the cell cycle, Two distinct processes contribute to restoration of chromatin structure during DNA replication, A fundamental problem in nucleosome assembly: histone-DNA aggregation, Chromatin Assembly Factor 1 (CAF-1) and PCNA, ASF1: a multi-talented histone chaperone, Biomedical implications, Agents that block the acetylation and deacetylation of new histones may sensitise cells to cancer chemotherapeutic agents, Genome-wide histone acetylation, deacetylation and epigenetic inheritance, Epigenetic xerox machines as potential targets for cancer therapy and regenerative medicine
Reviewed at 2019/12/04